Higiene bucal e fatores associados em idosos residentes em instituição de longa permanência - Montenegro, Luiza de Almeida Souto (2018)
To evaluate the oral hygiene status of institutionalized elderly people and the relationship of biofilm presence with socio-demographic characteristics, physical status, hygiene habits and presence of oral disorders, as well as to verify the association of biochemical and microbiological parameters with edentulism, presence of visible biofilm on teeth and prostheses. A cross-sectional study was carried out with 193 elderly people from seven long-term institutions in the metropolitan region of João Pessoa-PB. The number of teeth lost, the use of prostheses and the presence of visible biofilm on teeth and prostheses were analyzed through clinical examination. Samples of unstimulated saliva were quantified as volume, total proteins and microorganisms (Staphylacoccus sp., Streptococcus sp., Candida sp.). A chi-square test and hierarchical binary logistic regression model (α <0.05) were used to analyze biofilm association with sociodemographic characteristics, physical status, hygiene habits and presence of oral lesions and chi-square or exact test of Fisher to verify the association of the biochemical, microbiological parameters with edentulism, use of prosthesis and visible biofilm. The presence of dental biofilm (63.3%) is associated with age greater than 80 years (RP = 1.53, 95% CI = 1.02-2.23), presence of dental calculus (OR = 4.91, 95% CI 95 % = 2.13-11.35) and brushing frequency up to once daily (OR = 1.96, 95% CI = 1.15-3.33). The non-dominant hand strength below 12 kg (OR = 0.622, 95% CI = 0.39-0.98) and the oral hygiene performed by the caregiver (OR = 0.48, 95% CI = 0.25-0.91) were associated with the absence of biofilm. Associations were observed between the presence of biofilm in prostheses and the colonization of Streptococcus sp (p = 0.038). and Candida sp. (p = 0.03). Elderly people with reduced physical capacity for self-care have a lower biofilm frequency due to oral hygiene performed by the caregiver. Absence of teeth and use of prosthesis do not influence the biochemical and microbiological parameters. Biofilm in prostheses is associated with the quantification of Streptococcus sp. and Candida sp..